A Novel De-tert-butylation of p-tert-Butylcalix[n]arenes - Chennakesavulu, K.; Bhaskar Raju, G.; Prabhakar, S. (Asian Journal of Chemistry, 2010)
A facile de-tert-butylation method was developed for the synthesis of calix[n]arenes. A mixture of p-tert-butylcalix[n]arene, sodium dithionite and tri-fluoro acetic acid were refluxed at 80-90 ºC for 24 h. The calix[n]arenes with yields ranging from 80-92 % was achieved.